Measuring adherence levels to antiretroviral treatment (ART) and assessing certain factors affecting adherence in a state primary health care clinic, Mitchells Plain Community Health Centre, South Africa - Engel, Tania (Stellenbosch : Stellenbosch University, 2015)
Thesis (MMed)--Stellenbosch University, 2016